Contradições na espacialidade do Museu do Amanhã: o percurso do edifício e o percurso da curadoria - Malicheski, Isadora Finoketti; Aguiar, Douglas Vieira de (Pós. Revista do Programa de Pós-Graduação em Arquitetura e Urbanismo da FAUUSP, 2022)
The article offers an analysis of the Museum of Tomorrow in Rio from the standpoint of its spatial performance while receiving its users, the visitors. Spatial performance is referred to here as the way, either more or less appropriate or convenient that the user, the visitor, is received and guided in its pathway through the building. The interest in this building as an object of study is due, more than to its success of public or even to the peculiarity of its form, to subtler spatial aspects related to contradictions observed, by means of empirical research2, between the visitors’ pathway suggested by the building’s spatial configuration and the visitation route actually used by the visitor. The procedure of analysis adopted in what follows draws upon the walk, the architectural promenade, as a method of study. The article suggests, in conclusion, that the adopted visitation route works as a hindrance to the full architectural enjoyment that would be otherwise offered by the spatial configuration of this emblematic building.